Media populism in post-handover Hong Kong: an investigation of media framing of public finance. Issue 4 (2nd October 2017) - Tang, Gary
Abstract : Given that the political institution of Hong Kong is not fully democratic and is incompetent in channeling public opinion to the executive branch, the Hong Kong media perform the "surrogate democracy function, " wherein they act as the representative of the Hong Kong people in monitoring the government. This simultaneously provides a breeding ground for media populism. Focusing on newspaper editorials and reports on issues of public finance in Hong Kong, this paper analyzes the rhetoric of media populism, which has become part of the journalism culture of the city since the transfer of sovereignty. The paper reveals that media populism is formed by the construction of a populist diagnostic frame, which implies antagonism between the rich government and the deprived people. The populist diagnostic frame is exercised by (1) lexical creations that imply the government–people relation in public finance, (2) omitting inter-class redistribution by in-grouping both the middle class and the lower class as "the people, " and (3) validating the people's will by interpreting poll results.